2015
DOI: 10.1007/s12094-015-1468-7
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and management of breakthrough cancer pain: Have all the questions been resolved? A Delphi-based consensus assessment (DOIRON)

Abstract: Consensus was strong for most treatment, and diagnostic aspects were evaluated in the study. However, several important issues remain unresolved, particularly whether the diagnostic criteria must include strong opioids for background pain. Nurses' awareness and understanding of BTcP was considered insufficient, and more training is needed in this area. Overall, agreement among specialists was good, but more work is needed to better define the optimal diagnostic features and treatments for this condition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Nevertheless, most contemporary guidelines exclude end-of-dose pain/end-of-dose failure as a subtype of breakthrough pain, since this phenomenon represents a ‘failure’ of the around-the-clock/background medication 5–8. Moreover, there appears to be high agreement with this position among relevant healthcare professionals within Europe 9 10. In this study, 28% patients with breakthrough pain identified that ‘scheduled pain medication wearing off’ was a precipitant of their breakthrough cancer pain, which again suggests that many of these patients did not have adequately controlled background pain.…”
mentioning
confidence: 64%
“…Nevertheless, most contemporary guidelines exclude end-of-dose pain/end-of-dose failure as a subtype of breakthrough pain, since this phenomenon represents a ‘failure’ of the around-the-clock/background medication 5–8. Moreover, there appears to be high agreement with this position among relevant healthcare professionals within Europe 9 10. In this study, 28% patients with breakthrough pain identified that ‘scheduled pain medication wearing off’ was a precipitant of their breakthrough cancer pain, which again suggests that many of these patients did not have adequately controlled background pain.…”
mentioning
confidence: 64%
“…Constructs were rated on a 7-point Likert scale (i.e., 1-not at all important, 2-extremely low importance, 3-low importance, 4-slightly important, 5-moderately important, 6-very important, 7-extremely important/essential for all ACP studies). (32, 33) The panel was encouraged to use the full 7-point scale to prevent ceiling effects. Open-ended text boxes were provided for panelists to comment on the Organizing Framework domains, subdomains, and outcome constructs; to suggest new constructs; or to suggest whether constructs should be consolidated or deleted.…”
Section: Methodsmentioning
confidence: 99%
“…largely uniform, as suggested by the high degree of consensus reached in more than 80% of the items proposed. Two previous Spanish Delphi consensus ascertain the level of agreement among cancer pain specialists with the optimal definition, diagnosis, and management of BTcP, including a little section about BTcP follow-up [16,17]. The experts surveyed agreed that patients and adverse events should be assessed after starting BTcP medication within 48-72 h [17].…”
Section: Discussionmentioning
confidence: 99%